Islamic Education Teachers Strategy in Implementing Multiculturalism Based Education - Moh Padil; Fatimah Saguni; Adawiyah Adawiyah (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2021)
This study discusses teachers strategy of Islamic Education Implementing Multiculturalism Based Education. In conducting the study, we used a qualitative case study method. The case of this study was a stateb senior high school in Palu city. Data were gathered through direct field observation, in-depth interviews which involve teachers and the school principle. We also analyzed written material, such as the school teaching activities, to understand how the teacher strategies in implementing multicultural based education as the senior high school. Our study found that the teachers at the government senior high school made learning planning that emphasizes the integration of multicultural values, fairness, responsibility, religion, awareness of rights and obligations, equality, tolerance, respect for diversity, honesty, discipline contained in the learning program plan and in the syllabus. Then the implementation of multicultural education learning is carried out through a sociological approach that contains multicultural values.